IMPROVING STUDENTS’ READING COMPREHENSION THROUGH COOPERATIVE SCRIPT AT SMP NEGERI 21 MEDAN - Br PeranginAngin, Novi Indah Yanta; Rumapea, Linus; Ginting, Fiber Yunan (Kairos English Language Teaching Journal, 2020)
This study is intended to answer the problem in what way does the cooperative script improvement of students’ Reading Comprehension to the Eighth Grade Students’ of SMP Negeri Medan Jaya in the academic year 2016/2017. This study is classroom action research. The tools of data collection used observation, interview and test. On the first cycle the researcher used cooperative script to improve the students’ ability in comprehending on information of descriptive text about animal. The result of this research showed that the students ability in comprehending a descriptive text improved after applied the cooperative script. With this activity, students had more practice in reading. Besides, during the reading process students were active in asked and answered questions, this method also guide students to summarize the information of the passage. Consequently, the method successfully improved the students’ ability in reading comprehension of descriptive text.